Service Parts Inventory Management in a Branch Warehouse - Sripathomswat, Kanokporn; Torod, Kullavudh (Journal of Advanced Development in Engineering and Science, 2023)
This research aimed to propose spare parts inventory management policy using multi-criteria classification applying in a case study of forklift distributor company. Historical data of 101 spare parts in a branch warehouse were collected for one year. After data analyzing, multi-criteria spare parts classification was determined using both volume demand value and spare parts importance in term of criticality. Then, appropriate spare parts inventory management policies for each class were proposed in a considered branch warehouse of this case study such as Economics Order Quantity policy and Minimum-Maximum Order policy. According to the results, total cost of proposed policies was compared with the former. It showed that inventory management total cost of proposed policies was decreased for 23,378.87 baht or 15.76% in a studied sample spare part. Additionally, this proposed scheme can be applied in other spare parts warehouse in a similar way.